Pengaruh Penggunaan Perekat Epoxy Dan Phenolic Terhadap Kekuatan Impak Dan Keausan Pada Pembuatan Batu Gerinda - Wijanarko, Fuad, Bambang Waluyo F, ST., MT, Ir. Masyrukan, MT (2015)
Grindstone is a tool used for process cutting workpiece through the friction between the abrasive material abrasive to the workpiece. In addition to cutting the workpiece in accordance size, grinding process is also for finishing (smoothing and make accurate size on the surface of the workpiece). Hone may also aim to hone workpieces such as knives and chisels, and also to form a workpiece such as smoothing results cutting, smoothing welds, forming lengkunan on the workpiece angled, prepare the surface of the workpiece to weld. Grindstone primarily designed to complete a surface workpieces cylindrical, flat or settlement in the surface. In this study manufacture of grinding stone with a variety of adhesive type epoxy resin and resin phenolic compared with grinding stones that have no market brands LIPPRO aims to determine the quality of work millstone. The process of making millstones begins with the preparation of materials that will be used are epoxy resins, phenolic resins, cast iron slag mesh 12 and 40 mesh and fiberglass fibers. After that mix stone materials grinding accordance predetermined composition. Further compacted with a press machine with force of 3 tons for 1 hour. Then sintering with a temperature of 140ºC for 1 hour. Specimen testing performed is a wear test with standard ASTM D-3702, with the impact test ASTM E-23. From the research results show that the impact value and wear value of the grinding stone epoxy adhesive inversely with grinding stone phenolic adhesive. Grinding stone with epoxy adhesive has a level wear good but impaknya lower value. While millstone with phenolic adhesive has a good impact value but rates keausannya high. While millstone manufacturer brands have LIPPRO the degree of wear and impact value better than a stone grinding specimens designed by himself. Keywords: millstone, epoxy resins, phenolic resins